Improving paralympic development programs: Athlete and institutional pathways and organizational quality indicators - Hutzler, Y.; Higgs, C.; Legg, D. (Adapted Physical Activity Quarterly, 2016)
The article describes several approaches for improving Paralympic development programs. Particular focus is given to the vision of the International Paralympic Committee (IPC), as well as the IPC Strategic Plan 2015-18. Also mentioned are the Ostersund Declaration, long-term athlete-development model in Canada, Sports Policy factors Leading to International Sporting Success (SPLISS) model, and the USA Paralympic Sport Club Excellence Program.